2015
DOI: 10.1111/1750-3841.12877
|View full text |Cite
|
Sign up to set email alerts
|

Identifying Key Attributes for Protein Beverages

Abstract: This study identified key attributes of protein beverages and evaluated effects of priming on liking of protein beverages. An adaptive choice-based conjoint study was conducted along with Kano analysis to gain insight on protein beverage consumers (n = 432). Attributes evaluated included label claim, protein type, amount of protein, carbohydrates, sweeteners, and metabolic benefits. Utility scores for levels and importance scores for attributes were determined. Subsequently, two pairs of clear acidic whey prot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

8
54
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 52 publications
(63 citation statements)
references
References 46 publications
8
54
0
Order By: Relevance
“…ACBC cluster 1 was defined by a desire for high protein per serving, stevia as the primary sweetener, a desire for specifically whey protein products, and openness to ready‐to‐mix powder and peanut butter‐flavored products. These results strongly corroborate findings reported by Oltman et al (), which found that consumers driven by high protein amount also reported desires for low sugar content and openness to the use of natural non‐nutritive sweeteners. Demographically, cluster 1 had the highest proportion of male respondents, respondents who exercised 5+ times per week, and respondents who reported consumption of protein products for muscle building, compared to the other clusters.…”
Section: Resultssupporting
confidence: 91%
See 3 more Smart Citations
“…ACBC cluster 1 was defined by a desire for high protein per serving, stevia as the primary sweetener, a desire for specifically whey protein products, and openness to ready‐to‐mix powder and peanut butter‐flavored products. These results strongly corroborate findings reported by Oltman et al (), which found that consumers driven by high protein amount also reported desires for low sugar content and openness to the use of natural non‐nutritive sweeteners. Demographically, cluster 1 had the highest proportion of male respondents, respondents who exercised 5+ times per week, and respondents who reported consumption of protein products for muscle building, compared to the other clusters.…”
Section: Resultssupporting
confidence: 91%
“…Differentiation of groups in the CS survey (Figure ) was primarily dominated by three levels: all‐natural label claim (CS cluster 1), naturally sweetened (CS cluster 2), and no label claim (CS cluster 3). Preference within select consumer subgroups for protein products that are all‐natural or naturally sweetened is consistent with findings reported by Oltman et al () and Parker, Lopetcharat, and Drake (). Product attribute categories such as protein amount, protein type, and platform failed to define specific groups.…”
Section: Resultssupporting
confidence: 90%
See 2 more Smart Citations
“…Currently, there is a consumer trend for products with a higher protein content. In the United States, 54% of consumers try to incorporate more protein into their diets (Oltman et al, 2015). Regarding the advantages of protein products, there is convincing evidence about the benefits of higher protein intake in the health of specific population groups.…”
Section: Introductionmentioning
confidence: 99%